Von Willebrand’s disease mimicking postoperative bleeding after tibial nailing for tibial shaft fracture - Kadri Yildiz (Zaslavsky O.Yu., 2021)
Von Willebrand’s disease (VWD), or von Willebrand’s syndrome, is a bleeding syndrome characterized by low plasma levels of von Willebrand factor (VWF). VWD is the most common inherited human bleeding disorder. Partial quantitative deficiency of serum VWF is responsible for the majority of VWD cases. The effect of VWF deficiency on orthopedic operations is not well documented in the current literature. VWD may cause persistent bleeding during the operative and postoperative periods. In the majority of cases, VWD occurs as a single episode, but frequent relapses with chronicity can be seen in a small number of cases. We reported a case of a 22-year-old man with VWD operated with intramedullary nailing due to tibial shaft fracture. The patient had no previous history of surgery, and was unaware of his VWD. The purpose of this study is to report a rare complication of an orthopedic surgical procedure with postsurgical bleeding mimicking tibialis anterior arterial perforation. Orthopedic surgeons must be alert to the possibility of VWD due to postsurgical difficulties and persistent bleeding.